2016
DOI: 10.1002/cssc.201600895
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide: A Key Chemical for Today's Sustainable Development

Abstract: The global utilization of hydrogen peroxide, a green oxidant that decomposes in water and oxygen, has gone from 0.5 million tonnes per year three decades ago to 4.5 million tonnes per year in 2014, and is still climbing. With the aim of expanding the utilization of this eminent green chemical across different industrial and civil sectors, the production and use of hydrogen peroxide as a green industrial oxidant is reviewed herein to provide an overview of the explosive growth of its industrial use over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
267
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 447 publications
(270 citation statements)
references
References 28 publications
(43 reference statements)
1
267
0
2
Order By: Relevance
“…The global and strong demand of consumers for naturals, namely for functional products which are beneficial, and not harmful, both to health and to the environment, will continue to drive the demand of citric acid as ingredient in beverage, food, pharmaceutical and cosmetic products. Second, low price and abundance will originate a number of new, large-scale applications of the highly functionalized citric acid molecule, often in combination with other natural products and green chemicals, such as H 2 O 2 [48], to formulate new preservatives and antioxidants.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…The global and strong demand of consumers for naturals, namely for functional products which are beneficial, and not harmful, both to health and to the environment, will continue to drive the demand of citric acid as ingredient in beverage, food, pharmaceutical and cosmetic products. Second, low price and abundance will originate a number of new, large-scale applications of the highly functionalized citric acid molecule, often in combination with other natural products and green chemicals, such as H 2 O 2 [48], to formulate new preservatives and antioxidants.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…It is widely used in bleaching, chemical synthesis and water disinfection, with an annual production of about 5,000,000 t [1]. H 2 O 2 is currently produced in the so-called "anthraquinone" or "Riedel-Pfleiderer" process, developed between 1935 and 1945 [2], which is a complex procedure involving consecutive batch hydrogenation/oxygenation steps of anthraquinones.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This synthesis is highly coveted as it provides a greener, one step alternative to the traditional anthraquinone auto-oxidation process, which is a complex, multistep process with significant waste generation. 1315 Extensive research has shown that the most active catalysts for this reaction are Pd based, 16 and more recently bimetallic catalysts like Au–Pd, Pt–Pd, and Sn–Pd have come to the forefront for their superior performance. 1720 …”
mentioning
confidence: 99%